ASSESSING CROSS-CULTURAL UNDERSTANDING AND INTERCULTURAL COMMUNICATION SKILLS IN EFL CLASSROOMS: CHALLENGES, BEST PRACTICES, AND PERCEPTIONS - Yusi Rahmawati (NextGen Education Review Journal, 2023)
This research study explores the challenges and best practices in assessing cross-cultural understanding and intercultural communication skills in English as a Foreign Language (EFL) learners, considering both formative and summative assessment methods. Employing a mixed-methods research design, quantitative and qualitative data were gathered from EFL teachers and learners in diverse cultural settings. The findings reveal a variety of assessment tasks commonly used, such as written assignments, oral presentations, group discussions, and cultural projects, to evaluate cross-cultural competence. Formative assessment methods, including self-reflection, peer feedback, and teacher-student conferences, were prevalent in assessing cross-cultural understanding. Challenges in cross-cultural assessment include developing culturally sensitive tasks and rubrics, addressing biases in assessment instruments, balancing language proficiency and cultural understanding, and ensuring fairness and inclusivity. Best practices identified include providing clear assessment criteria, incorporating authentic tasks, promoting self-reflection and peer feedback, integrating multiple assessment methods, and offering professional development for teachers. The study emphasizes the positive perceptions of both teachers and learners regarding the effectiveness of cross-cultural assessment in promoting intercultural competence. By addressing these challenges and implementing recommended practices, educators can enhance the quality of EFL education and better prepare learners for effective communication in diverse cultural settings.